(untitled) (Серія: Історія. Політологія, 2025)
Стаття присвячена аналізу політичних стереотипів як інструменту гібридної війни Російської Федерації проти України. Визначено, що стереотипи формують спрощені та емоційно забарвлені образи, які полегшують маніпуляцію суспільною свідомістю, сприяють поляризації, підривають довіру до державних інститутів та дестабілізують внутрішні відносини. Проаналізовано основні стереотипи, які просуваються РФ в українському суспільстві, на тимчасово окупованих територіях, серед росіян та західних союзників, визначено їх специфіку та особливості впливу на кожну з зазначених груп. Відзначено, що історично закріплені образи українців трансформуються у сучасні пропагандистські наративи, а цифрові технології значно посилюють їхнє поширення. Підкреслено необхідність подальших досліджень механізмів формування та закріплення стереотипів у цифровому середовищі та розробки стратегій протидії деструктивним наративам, що сприятиме національній консолідації та посиленню міжнародної підтримки України. The article presents a comprehensive analysis of political stereotypes as a deliberate and strategically employed instrument of the Russian Federation’s hybrid war against Ukraine. It demonstrates that, in the context of contemporary information and psychological confrontation, political stereotypes serve as a powerful tool of manipulative influence on public consciousness, creating simplified, emotionally charged, and easily reproducible images that penetrate diverse social groups and shape collective perceptions. These stereotypes are systematically deployed by Russia to undermine social cohesion, erode trust in state institutions, exacerbate internal conflicts, and intensify polarization within Ukrainian society. Particular attention is given to stereotypes regarding internally displaced persons, veterans, and residents of specific regions, which exert a profoundly destabilizing effect on processes of national consolidation, social integration, and the development of shared civic identity. The study traces the historical roots of political stereotypes - from imperial and Soviet-era narratives («Little Russian», «Khokhol», «Banderite») to contemporary ideological constructs («Nazis», «punishers», «incapable state») - which have been adapted and transformed into powerful instruments justifying aggression and legitimizing Russia’s political and military ambitions. It examines the mechanisms through which stereotypes are constructed and reinforced in mass consciousness, including the simplification of complex political and social phenomena, the emotional amplification of selective traits, and systematic mythologization along the «us versus them» principle. The analysis highlights the crucial role of digital technologies, social media, and online platforms in accelerating the dissemination of stereotypical images, creating virtual group identities, and fostering intergroup confrontation and division. Moreover, the article notes that Russia actively exploits pre-exising biases, fears, and misperceptions among Ukraine’s Western partners, leveraging concerns about the «incapacity of Ukraine», the «impossibility of achieving victory», or the «risks of destabilizing Russia» to reduce political, economic, and military support. This international dimension underscores the global reach and strategic impact of information warfare based on stereotypes. The study concludes that political stereotypes pose a significant threat not only to Ukraine’s internal stability and social cohesion but also to the effectiveness of international support for its defense against aggression. The article emphasizes the urgent need for interdisciplinary research on political stereotypes within the framework of information warfare and the development of comprehensive strategies to counteract their destructive influence. Such efforts would mitigate the adverse effects of propaganda, reinforce national unity, strengthen resilience against social and political manipulation, and promote a positive and credible international image of Ukraine while enhancing the capacity to withstand ongoing information threats.